Seychelles : Second Review Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Financing Assurance Review; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report, 2009)
This paper presents key findings of the Second Review for Seychelles under the Stand-By Arrangement. The program is on track, and macroeconomic stabilization has advanced rapidly. The authorities are implementing the program with determination and a high degree of ownership. All quantitative performance criteria at end-March 2009 were met. One of two structural benchmarks for end-April was missed, reflecting capacity constraints in issuing new bank capitalization norms, but was completed in late May.